Development of Cultural And Religious Tourism Villages In Enhancing Rural Community Welfare - Chusmeru Chusmeru; Tri Nugroho Adi; Ganjar Agus Runtiko; Adhi Iman Sulaiman; Petrus Imam Prawoto Jati; Sri Weningsih; Niken Hapsari Arimurti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The improvement of rural community welfare is not solely dependent on successful agricultural development but can also be driven by the potential and uniqueness of natural and cultural tourism within rural communities. Thus, it is essential to study cultural and religious tourism villages that can be developed to enhance rural community welfare. This research was conducted in Kalisalak Village, Kebasen District, Banyumas Regency, which serves as a cultural and religious tourism village. The research utilized a case study approach to construct factual realities by collecting data through direct observation, interviews, and focus group discussions. The analysis involved data reduction, confirmation, and triangulation. The findings indicate that the Curug Song and Telaga Anteng tourist sites have the potential to be developed into eco-tourism attractions, maintaining their natural beauty and environmental preservation. The historical site and sacred keris bathing sites offer the potential for educational tourism, providing historical literacy, philosophy, and the preservation of local wisdom, which is passed down across generations to foster harmony, peace, solidarity, and wisdom. These two tourism potentials can be developed through community empowerment programs designed to manage and sustain eco-tourism and educational tourism that is green, environmentally friendly, and sustainable.